Acrida bara, synomymous with A. sulphuripennis (Orthoptera, Acrididae, Acridinae) - Claudia Hemp (Journal of Orthoptera Research, 2023)
The male holotype of Acrida bara Steinmann, 1963 from the Budapest collection (HNHM) was studied and found to be identical to Acrida sulphuripennis (Gerstaecker, 1869). Consequently, Acrida bara syn. nov. is synonymized with A. sulphuripennis.